Optimisation and analysis of system integration between electric vehicles and UK decentralised energy schemes. (1st June 2019) - Chakrabarti, Auyon; Proeglhoef, Rafael; Turu, Gonzalo Bustos; Lambert, Romain; Mariaud, Arthur; Acha, Salvador; Markides, Christos N.; Shah, Nilay
Abstract: Although district heat network schemes provide a pragmatic solution for reducing the environmental impact of urban energy systems, there are additional benefits that could arise from servicing electric vehicles. Using the electricity generated on-site to power electric vehicles can make district heating networks more economically feasible, while also increasing environmental benefits. This paper explores the potential integration of electric vehicle charging into large-scale district heating networks with the aim of increasing the value of the generated electricity and thereby improving the financial feasibility of such systems. A modelling approach is presented composed of a diverse range of distributed technologies that considers residential and commercial electric vehicle charging demands via agent-based modelling. An existing district heating network system in London was taken as a case study. The energy system was modelled as a mixed integer linear program and optimised for either profit maximisation or carbon dioxide emissions minimisation. Commercial electric vehicles provided the best alternative to increase revenue streams by about 11% against the current system configuration with emissions effectively unchanged. The research indicates that district heating network systems need to carefully analyse opportunities for transport electrification in order to improve the integration, and sustainability, of urban energy systems. Highlights: Framing of a modern district energy system as a mixed integer linear program. Agent-based modelling used to simulate electric vehicle charging demands. Electric vehicle charging in a district heating network simulated for a London area. District heating integration with electric vehicles improves revenues by 11%.